1988
DOI: 10.1038/bjc.1988.85
|View full text |Cite
|
Sign up to set email alerts
|

Loss of polymorphic A and B locus HLA antigens in colon carcinoma

Abstract: In the present study we have confirmed that approximately one third of human colorectal carcinomas fail to express the HLA - A,B,C monomorphic determinant reactive with the W6/32 MAb, and 44% express class II HLA antigens as shown by reactivity with NFK-1 MAb. Reduced staining with the W6/32 MAb was not always associated with the loss of beta 2m. In addition, the expression of HLA-A2 and Bw4 class I specific haplotypes on normal colon epithelium and tumour biopsy tissue was assessed. All normal colonic epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
13
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 19 publications
4
13
0
Order By: Relevance
“…In vitro tests seem to indicate that MHC class I antigen expression on tumour cells is more relevant for putative in vivo tumour cytotoxicity by T-cells than class II antigens. The differential expression of MHC class I antigens has recently been described in colorectal carcinomas (Rees et al, 1988;Smith et al, 1988;LopezNevot et al, 1989;Momburg et al, 1989), gastric and laryngeal carcinomas (Lopez-Nevot et al, 1989) and breast carcinomas (Muller & Stutte, 1988). An impact of MHC class I subtypes on the clinical course of human breast carcinomas is suggested by the latter group, who demonstrated that HLA-A2 expression in breast carcinomas is conversely related to the number of axillary lymph node metastases.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro tests seem to indicate that MHC class I antigen expression on tumour cells is more relevant for putative in vivo tumour cytotoxicity by T-cells than class II antigens. The differential expression of MHC class I antigens has recently been described in colorectal carcinomas (Rees et al, 1988;Smith et al, 1988;LopezNevot et al, 1989;Momburg et al, 1989), gastric and laryngeal carcinomas (Lopez-Nevot et al, 1989) and breast carcinomas (Muller & Stutte, 1988). An impact of MHC class I subtypes on the clinical course of human breast carcinomas is suggested by the latter group, who demonstrated that HLA-A2 expression in breast carcinomas is conversely related to the number of axillary lymph node metastases.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous report we have documented the loss of both monomorphic and polymorphic HLA class I determinants in human colon carcinoma (Rees et al, 1988); in several cases primary tumours that stained with mAb W6/32 failed to stain with a mAb specific for the appropriate haplotype (A2 or Bw4). The presence study evaluates further the expression of HLA class I molecules in primary and metastatic deposits from individual patients with colon or breast carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have now shown that many human tumours fail to express antigens recognised by monoclonal antibodies (mAbs) specific for the monomorphic sites of HLA class I molecules (Masucci et al, 1987;Smith et al, 1988;Broker et al, 1984;Lopez-Nevot et al, 1989;Momburg et al, 1986;Momburg & Koch, 1989;Muller & Stutte, 1988;Natali et al, 1983;Perez et al, 1986). Furthermore, some primary human colon carcinomas fail to express HLA class I polymorphic regions (Rees et al, 1988;Momburg & Koch, 1989); the absence of these haplotypes may also be significant.…”
mentioning
confidence: 99%
“…Thus, the selective loss of class I polymorphic determinants described in this study could be an effective mechanism for the tumor to escape both CTL recognition and natural killer surveillance simultaneously. Alteration in expression of polymorphic HLA class I determinants in tumors does not appear to be restricted to HLA-A2 epitopes since decreased expression of HLA-B determinant has been reported in a small number of colorectal tumors (26,27). The malignant transformation of different cell types may be associated with distinct changes in expression of HLA class I loci.…”
Section: Discussionmentioning
confidence: 99%